1971
DOI: 10.1063/1.1675507
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Na+, K+, and Ba+ Ions with O2, NO, and H2O Molecules

Abstract: Ion–molecule reactions of sodium, potassium, and barium ions with O2, NO, and H2O have been studied in a drift tube–mass spectrometer apparatus. The following rate constants or upper limits were obtained: Na+,K, +, Ba++O2(NO)→products, k < 10−13cm3/sec (0.04 − ∼ 5 eV), Na++H2O+M→Na+·H2O+M, k(3) = 1.0(+ 0.5, − 0.3) × 10−28cm6/secfor M = H2O, k(3) = 4.7(+ 1.2, − 1.0) × 10−30cm6/secfor M = He, K++H2O+M→K+·H2O+M, k(3) = 4.5(+ 2.3, − 1.5) × 10−29cm6/secfor M = H2O, k(3) = 2.6(+ 0.7, − 0.5) × 10−30cm6/secfor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…The results are listed in Table . Note that the estimated value of k 5 is in accord with an upper limit of 2 × 10 -30 cm 3 molecule -1 s -1 measured in a drift tube experiment . For the association of K + and O, k 6 was estimated using the same parameters for 〈Δ E 〉 down and n .…”
Section: Rrkm Calculations On the K+ + X Recombination Reactionssupporting
confidence: 68%
“…The results are listed in Table . Note that the estimated value of k 5 is in accord with an upper limit of 2 × 10 -30 cm 3 molecule -1 s -1 measured in a drift tube experiment . For the association of K + and O, k 6 was estimated using the same parameters for 〈Δ E 〉 down and n .…”
Section: Rrkm Calculations On the K+ + X Recombination Reactionssupporting
confidence: 68%
“…Surprisingly, to the best of our knowledge, there are no previous reports on the reactions of Ln + with water, although gas‐phase reactions between water and other metal cations have been surveyed by several groups 16. As early as 1971, Biondi et al17 reported the first measurement of the reactions of K + and Na + with water. Reactions of first‐row transition metal cations with water have been surveyed by the Armentrout research group16b, 18 using guided ion‐beam mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, a systematic study of the literature for bimolecular gas phase cation-molecule reaction kinetics 16 revealed that O 2 could be used as an alternative to NH 3 for the interference-free or at least less-interfered determination of K 1 . Indeed, while K 1 shows no reactivity towards O 2 , 17 the reaction of the interfering ArH 1 with O 2 is thermodynamically allowed and fast. 15 Under optimised conditions, the signal-tobackground-ratio for K could also be improved by a factor of 20 by using O 2 .…”
Section: Resultsmentioning
confidence: 99%